Infective endocarditis as a morbidity predictor in patients who underwent mitral valve surgery - Supomo Supomo; Kelik Wagiyanto; Aditya Agam Nugraha (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Infective endocarditis (IE) often develops into rheumatic heart disease (RHD) that has many perioperative complications during the evolution of the disease. Cardiac surgery in patients with IE is often followed by post-operative morbidities that can decrease the quality of life. This study aimed to investigate the correlations between preoperative IE and the emergence of various morbidities in patients undergoing heart valve surgery. This was a cross-sectional study with secondary data analysis of the medical record in 60 patients with mitral valve surgery at Dr. Sardjito General Hospital, Yogyakarta from 2012 to 2017. As much as 30 of 60 patients were suffered IE before mitral valve surgery. The most common valve disease in the IE group was mitral stenosis (60%). IE was significantly associated with arrhythmia and cardiac event with p=0.002 (PR: 6.91), prolonged ICU stay with p=0.011 (PR: 5.68), prolonged ventilator use with p=0.015 (PR: 12.43) and severe pulmonary arterial hypertension (PAH) with p=0.033 (PR: 0.192) post mitral valve surgery. As many as 26 (87%) and 29 (96.7%) of patients with IE had a prolonged ICU stay and prolonged ventilator after mitral valve surgery respectively. The incidence of severe PAH postoperatively in the IE group was lower than in the non-IE group (10% vs 36.7%). IE was significantly associated with the increased risk of arrhythmia, prolonged ventilator use and prolonged ICU stay after mitral valve surgery